La Responsabilidad Civil en el Perú: avances, críticas y asuntos pendientes - Cieza Mora, Jairo (2020)
ADVOCATUS had the opportunity to interview three Peruvian lawyers of great experience to share their insight on Tort Law in our legal framework.